Beyond Courses: Towards Supporting Goal-Oriented Learning in MOOC Platforms - ALSaad, Fareedah; Alawini, Abdussalam (Proceedings - Frontiers in Education Conference, 2023)
Existing Massive Open Online Course (MOOC) platforms limit their course offering to degree programs and certifications. The course design of existing MOOCs adopts a one-size-fits-all pedagogy where all learners watch the same video lectures and complete the same assignments regardless of their learning goals or background. However, research shows that MOOC learners may have none-traditional learning goals, such as exploring a course or learning specific concepts within a course. The design of current MOOC platforms lacks support to learners who want to utilize MOOCs as modularized resources instead of regular courses. Learners need to manually locate the educational materials that address their learning goals which can be time-consuming and sometimes confusing. To support the diverse needs of MOOC learners, we introduce a customized learning approach, CustomLearn, which facilitates goal-oriented learning in MOOC platforms. Our approach of customizing learning proposes four learning goals: Exploring (explore a subject), Conforming (learn popular topics in a subject), Mastering (being expert in a subject), and Personalizing (creating a personalized study plan). These learning goals use subjects to deliver customized learning plans that span multiple courses. Thus, the customized learning approach organizes similar courses to make the educational materials easily accessible by learners. To assess our proposed customized learning approach, we developed an early prototype of CustomLearn and used it to conduct a user study with MOOC learners to evaluate the viability of CustomLearn and learners' acceptability of heterogeneous study plans. Our evaluation indicated that CustomLearn is a viable approach, evident by participants' high perceptions of the usefulness of CustomLearn and their willingness to use and recommend it if offered by MOOC platforms. Additionally, most participants found heterogeneous study plans acceptable for learning any topic as long as these plans maintain high instructional quality.